Differences in life space area between older non-cyclists, conventional cyclists and e-bikers. (September 2019) - Van Cauwenberg, Jelle; Schepers, Paul; Deforche, Benedicte; de Geus, Bas
Abstract: Purpose: Conventional and electric bicycles (e-bikes) offer a non-polluting and physically-active alternative to cars to support older adults' access to different life spaces. We aimed to provide an initial exploration of the relationship between cycling status (non-cyclist, conventional cyclist or e-biker) and life space area. Additionally, we examined whether this was moderated by sex, functional health and car driving. Methods: Cross-sectional survey data on socio-demographics, health characteristics, transport behavior and life space area were collected among 1, 333 Dutch and Flemish older adults (≥65 years). Generalized linear models were used to examine the relationship between cycling status and life space area. Results: After adjustment for socio-demographic, health and transport variables, conventional cyclists (b = 1.40, SE = 0.29, p < 0.001) and e-bikers (b = 1.59, SE = 0.29, p < 0.001) had larger life space areas compared to non-cyclists. The difference in life space area between conventional cyclists and e-bikers was non-significant (b = 0.19, SE = 0.28, p = 0.49). The relationship between cycling status and life space area was not significantly moderated by sex (chi 2 = 0.82, p = 0.66), functional health (chi 2 = 1.61, p = 0.45) and car driving (chi 2 = 1.96, p = 0.38). Conclusion: Initiatives aimed at promoting conventional cycling as well as e-biking may offer an effective strategy to expand older adults' life space area. Future longitudinal and experimental research using objective assessments of life space area is warranted to examine the causal effects of conventional cycling and e-biking on life space area. Highlights: Conventional cyclists and e-bikers have larger life space areas than non-cyclists. No difference in life space area between conventional cyclists and e-bikers. Findings do not differ according to gender, functional health and car driving. Promoting conventional cycling and e-biking may expand older adults' life space area.